Contrast-enhanced ultrasound as a valuable tool to detect minimal inflammation in RA patients in sustained remission - Polido-Pereira, Joaquim; António, Manuel S.; Khmelinskii, Nikita; Arese, Marta; Teixeira, Rui; Vieira-Sousa, Elsa; D'Agostino, Maria A.; Fonseca, João E. (Frontiers in Medicine, 2024)
Objective The study aimed to explore the utility of contrast-enhanced ultrasound (CEUS) as a tool for detecting minimal inflammation in rheumatoid arthritis (RA) patients in sustained remission (SR) and to correlate the findings with Disease Activity Score 28 (DAS28) status scores and various ultrasound (US) scores. Patients and methods Thirty RA patients in SR (minimum 6 months), 12 with active disease, and 10 healthy controls were included. Clinical evaluations and US assessments were performed, including grayscale US (GSUS), power Doppler US (PDUS), and Global OMERACT-EULAR Synovitis Score (GLOESS). The CEUS was performed in the two most active joints and was scored semi-quantitatively (SQ) and quantitatively. Results Healthy controls and remission RA patients had similar total US scores. Active RA patients had higher US scores than the healthy and remission groups, with statistically significant differences in all the groups compared to the healthy group. However, significant differences were only observed in the GSUS and GLOESS when comparing active RA patients with the remission group. Ninety-five joints were selected for the CEUS, and we detected more microvascularization with the SQ CEUS score than with the PDUS in all groups (18 vs. 58% in the remission group; p-value 0.006). The weighted Cohen's kappa for the intra-rater and inter-rater IACUS CEUS score was 0.714 (confidence interval 0.610–0.819, p-value < 0.001) and 0.540 (confidence interval: 0.419–0.662, p-value < 0.001), respectively. Spearman's correlation between the SQ CEUS and quantitative scores was 0.655. Conclusion For the majority of RA patients in SR, conventional US may fail to detect microvascularization potentially related to the subclinical disease. The CEUS may be helpful for this purpose.